2017
DOI: 10.1093/schbul/sbx100
|View full text |Cite
|
Sign up to set email alerts
|

Improving Work Outcome in Supported Employment for Serious Mental Illness: Results From 2 Independent Studies of Errorless Learning

Abstract: These data support errorless learning as an adjunctive intervention to enhance supported employment outcomes and implicate the relevance of workplace social difficulties as a key impediment to prolonged job tenure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…These data were similar to those in original WBI validation studies (Bryson et al, 1999; McGuire et al, 2007), but do not include current recommended competitive employment outcomes (Drebing et al, 2012). However, some recent research suggests WBI ratings (based only on supervisor interview) predicted job tenure in SE (Kern et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data were similar to those in original WBI validation studies (Bryson et al, 1999; McGuire et al, 2007), but do not include current recommended competitive employment outcomes (Drebing et al, 2012). However, some recent research suggests WBI ratings (based only on supervisor interview) predicted job tenure in SE (Kern et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It includes a worksite behavioral observation, and a semi-structured interview with work supervisors. It has strong psychometric properties (Bryson et al, 1997; Bryson et al, 1999; Bull et al, 2015) and has been widely used as a functional measure in schizophrenia (Kukla et al, 2018; Kern et al, 2018; Mervis et al, 2017; McGuire et al, 2007). It has demonstrated sensitivity to change in vocational rehabilitation (VR) intervention trials (Bell et al, 2003; Bryson et al, 2003), a characteristic necessary for assessment of functional outcomes (Bellack et al, 2007; Mausbach et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by being adequately rewarded and motivated with individualized options, the participants were positively occupied, and the learning process was fostered. [47,48] Third, participants with schizophrenia spectrum were constructively engaged. That is, by designing an usertailored rehabilitative strategy, they were focalized on new adaptive skills.…”
Section: Discussionmentioning
confidence: 99%
“…While employment placement rates have been reported in all studies, employment duration has been reported less frequently. This is notable as supporting sustained employment has been identified as a continuing challenge in IPS programmes (Kern et al, 2018).…”
Section: Introductionmentioning
confidence: 99%